Environmental health risk analysis from detergent contamination in well water - Muhammad Arinal Surgama Yusuf; Anwar Mallongi; Anwar Daud; Agus Bintara Birawida; Sukri Palutturi; Lalu Muhammad Saleh; Setiawan Kasim (AIMS Environmental Science)
High concentrations of detergent waste disrupt aquatic biota. Detergent content can increase nutrient levels, causing environmental problems. The purpose of this study was to determine the level of public health risk in Lamangga Village, Baubau City, where well water containing phosphate and surfactants is consumed. This was an observational study with environmental health risk analysis. The study was composed of representative samples from 14 wells used as a source of drinking water and 70 respondents. The results showed that the average concentration of phosphate in drinking water sources across the 14 sampling points was 0.020 mg/L and that of surfactants was 0.39 mg/L. The rate of exposure to detergent concentration in raw water (intake rate) is directly proportional to the risk level value (RQ). The RQ of all respondents was ≤ 1. All 70 respondents had a target hazard quotient (THQ) ≤ 1, and no respondents had a THQ value higher than 1. The standardization values issued by the US-EPA Agency and the Regulation of the Minister of Health of the Republic of Indonesia Number 32/2017 set the reference dose (RfD) value of surfactants and phosphate at 0.05 mL/L/d. Surfactant exposure can cause irritation to the skin and eyes and damage the skin's natural protective layer, while phosphate exposure is not directly toxic to humans in small concentrations. Risk management strategies are necessary to control phosphate and surfactant concentrations in drinking water so that they do not result in future non-carcinogenic risk effects.